Design and development of rotating-sleeve refrigerant compressor - Musa, Md. Nor (Universiti Teknologi Malaysia, 2002)
A Single Vane Rotating Sleeve compression concept a patent of which has been filed by UTM, is the main focus of this study. Research and development on the concept was carried out to investigate its feasibility on a refrigeration system. The concept was designed based on the specifications of the existing reciprocating compressor installed in a refrigerator. In order to design a functional prototype, the author has conducted literature study on existing rotary compressor models such as rolling piston and sliding vane types that are used in room and car air conditioning systems respectively. The literature study is crucial in areas such as the geometrical optimization, material selection, tolerance and surface finishing in designing the prototype. Preliminary concept development and design are also conducted for the new concept investigating critical design data for used in future research. Further research and development however is needed to improve the compressor performance up to a commercial acceptable level.